Anak Berkebutuhan Khusus dalam Psikologi Pendidikan Islam - Rohimah, Siti; Sanusi, M.; Ghafur, Octa Abdul; Ardianto, Risko Aris (Lembaga Yasin AlSys, 2024)
This article discusses ABK in Islamic psychology. The aim is to find out the extent to which Islam views ABK, as well as finding out educational solutions for ABK from an Islamic perspective. This research uses a literature review approach from several book sources, journal articles and websites. The results of the research show ABK's views on Islam, solutions to Islamic education for ABK, as well as supporting and inhibiting factors for Islamic education for ABK.